2014
DOI: 10.1186/1754-1611-8-17
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hydromechanical stress in aerated stirred tanks up to 40 m3 scale by measurement of maximum stable drop size

Abstract: BackgroundTurbulence intensity, or hydromechanical stress, is a parameter that influences a broad range of processes in the fields of chemical engineering and biotechnology. Fermentation processes are often characterized by high agitation and aeration intensity resulting in high gas void fractions of up to 20% in large scale reactors. Very little experimental data on hydromechanical stress for such operating conditions exists because of the problems associated with measuring hydromechanical stress under aerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Hydrodynamic characteristic of the fermentation system is one of the external factors responsible for the metabolism rate of cells [ 3 , 4 , 9 ]. It has been discussed for a long time to have large influence on biological process [ 18 ], cell viability, and product titers [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrodynamic characteristic of the fermentation system is one of the external factors responsible for the metabolism rate of cells [ 3 , 4 , 9 ]. It has been discussed for a long time to have large influence on biological process [ 18 ], cell viability, and product titers [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays advantages in fluid mechanics enable us to gain a more in-depth insight into the complex effects of agitation processes. Models have been successfully exploited in determining the correlationship between agitation and fermentation process, such as maximum stable (equilibrium) drop size in intermittent turbulence [ 8 , 9 ], hydrodynamic stress [ 10 ], eddy length [ 11 ], and energy dissipation [ 12 ]. At the same time, developments on metabolic flux analysis (MFA) also allows for the systematical elucidation of cellular behaviors [ 13 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, determination of the k L a in bioreactors is an important parameter when assessing the oxygen mass transfer characteristics in connection with mixing and reactor geometry. In STRs, the increase of k L a implies vigorous stirring to favor mass transfer from gas to liquid phase by increasing the turbulence of the system, thus increasing shear stress on the medium and cells [27,28]. In contrast, wave and rocking-motion reactors are characterized by up to 100-fold lower shear forces compared to STRs [21,22,29] and especially 2D rocking-motion bioreactors provide higher k L a values compared to simple wave systems that are comparable to those obtained in STRs at high stirring speed [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…for the different operating conditions and impellers apart from the wave-ribbon impellers, which is well in agreement with literature data in the range of 0.56−0.61 for breakup controlled dispersion systems. 2,47,48 It is concluded that in the investigated coalescence inhibited dispersion system, the hydromechanical stress caused by various impellers can be quantified only by examining volume-based drop size distributions. The Sauter mean diameter d 32 , as a volume-based averaged size, emphasizes the changes of the large droplets with the time, the power input, and the impeller type.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%